(untitled) (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the income of coconut farming in Makawidey Village, Aertembaga District, Bitung City. This research was conducted for 2 months, from March to May 2022. The data analysis method used in this study was quantitative analysis. Quantitative analysis used is the analysis in determining production, revenue, costs and income. The data used are primary data and secondary data. Primary data was obtained through direct interviews with farmers who own coconut land and those who cultivate coconuts using a prepared questionnaire and observation in the field. Secondary data were obtained from agencies related to this research. The results showed that the income of coconut farming in Makawidey Subdistrict, Aertembaga District, Bitung City with the coconut management fee system was IDR3,764,689 per farmer and income per hectare was IDR1,792,964. Coconut farming income by processing the profitsharing system is IDR3,058,539 per farmer, and IDR1,456,475 per hectare. Coconut processing with a wage system is greater than the profitsharing system.